2017
DOI: 10.1098/rspb.2017.0380
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ageing, costs of reproduction and the fecundity–longevity trade-off in eusocial insects

Abstract: Eusocial insects provide special opportunities to elucidate the evolution of ageing as queens have apparently evaded costs of reproduction and reversed the fecundity–longevity trade-off generally observed in non-social organisms. But how reproduction affects longevity in eusocial insects has rarely been tested experimentally. In this study, we took advantage of the reproductive plasticity of workers to test the causal role of reproduction in determining longevity in eusocial insects. Using the eusocial bumbleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…Comparing milkweed species that vary more substantially in cardenolide toxicity, we found that host plants with increased and more nonpolar cardenolides have negative effects on A. nerii development and fecundity, consistent with other studies that have demonstrated that plant species characterized by more toxic cardenolides are negatively associated with A. nerii population growth (Agrawal, ; Colvin, Snyder, & Thacker, ; de Roode et al., ). In the first fitness experiment, there was evidence of greater longevity on more highly defended plants (Figure e), perhaps indicative of trade‐offs between fecundity and longevity (Blacher, Huggins, & Bourke, ; Miyatake, ). However, we interpret this result with caution, both because the effect was not replicated in the second experiment (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Comparing milkweed species that vary more substantially in cardenolide toxicity, we found that host plants with increased and more nonpolar cardenolides have negative effects on A. nerii development and fecundity, consistent with other studies that have demonstrated that plant species characterized by more toxic cardenolides are negatively associated with A. nerii population growth (Agrawal, ; Colvin, Snyder, & Thacker, ; de Roode et al., ). In the first fitness experiment, there was evidence of greater longevity on more highly defended plants (Figure e), perhaps indicative of trade‐offs between fecundity and longevity (Blacher, Huggins, & Bourke, ; Miyatake, ). However, we interpret this result with caution, both because the effect was not replicated in the second experiment (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…While specialized life history strategies are widely recognized (Sibly and Brown 2009), birth rates are governed by metabolic scaling (Lindstedt and Calder 1981) and are not easy to change permanently without physiological tradeoffs. Elevated reproductive rates lead to shortened lifespan, as limited resources enforce a compromise between investment in reproduction and somatic maintenance (Edward and Chapman 2011, Blacher et al 2017).…”
Section: Demographic Paths To Evolutionary Expansionmentioning
confidence: 99%
“…Reproduction itself is central to the Evolution of species [1]. Indeed, it is the slow drift of genotypes along successive generations of living species that gives rise to increasing variability of individuals, and occasio to speciation [2][3][4][5][6]. Speciation occurs when individuals from the same original species become unable to interbreed (and thus do not reproduce).…”
Section: Introductionmentioning
confidence: 99%